Language to language a practical and theoretical guide for Italian/English translators - Taylor, Christopher (Cambridge University Press, 1998)
Language to Language is for students of English/Italian translation and practising translators. Part One provides a theoretical background, examining the relevance of the study of lexis, semantics, pragmatics, culture, stylistics and genre to translation. This section includes numerous practical examples of how the translator's thought processes are brought to bear to solve translation problems in specific texts. Part Two contains a wide selection of texts prepared for pre-translation analysis and translation proper. The method adopted is designed to illustrate the translation process rather than the translation product. Texts are taken from a variety of sources including: literature, technical and scientific material, tourist information, promotion and advertising, legal contracts, business letters, film dubbing, newspapers. Further texts are then provided for translation practice.